Learning and Training of Coal-Fired Energy using Augmented Reality (C-FAR) - Norshahidatul Hasana Ishak; Nur Farahin Johari; Siti Nuramalina Johari; Hazrati Zaini; Abdul Hasib Sadiqin Adam Shukri; Aqil Afifi Ahmad Senusi (Journal of Advanced Research in Computing and Applications, 2023)
Renewable energy resources are something that can be reloaded or refilled by the surroundings in small times. This resources consider reliable to use because the resources usually renew so fast that until it been renewed by the time people used up. In Malaysia, both renewable and non-renewable resources were used to generate an electricity to the consumer. The use of electrical energy has been increased. Thus, all of the electrical power station required many specialist engineers in order to produce the electrical energy at optimum level. However, the learning and training method of producing specialist engineers are based on printed material. Therefore, this project has decided to design and develop an interactive learning and training of handling a machine using augmented reality approach towards the recently hired employee. The learning process involve an interactive 3D images that represents the actual machine from the real life environment. PADDIE method was used in developing the application. Because it is flexible and suitable as this project implement AR as a platform for learning and training process to occur. PADDIE model consists of six phases which are planning, analysis, design, develop, implement and evaluation. Preliminary study has been done as a starting point for this project. After complete the development of the project, evaluation is conducted to evaluate the user acceptance of the product towards the workers. Based from the result of user acceptance testing evaluation, majority of the workers strongly agree that this project can be use and adapt towards the real life working environment. As for future use, some improvement can be applied such as put more models of the machine, use a tablet instead of mobile phone and the application can be publish in other platform for example iOS.